56.3k views
2 votes
8-6x+11+3x+4x-5=5+3×4

User Jacklyn
by
5.6k points

2 Answers

3 votes

Answer:

x = 3

Explanation:

Solve for x:

4 x + 3 x - 6 x - 5 + 8 + 11 = 3×4 + 5

3×4 = 12:

4 x + 3 x - 6 x - 5 + 8 + 11 = 12 + 5

Grouping like terms, 4 x + 3 x - 6 x - 5 + 8 + 11 = (-6 x + 3 x + 4 x) + (8 + 11 - 5):

(-6 x + 3 x + 4 x) + (8 + 11 - 5) = 5 + 12

-6 x + 3 x + 4 x = x:

x + (8 + 11 - 5) = 5 + 12

8 + 11 - 5 = 14:

x + 14 = 5 + 12

5 + 12 = 17:

x + 14 = 17

Subtract 14 from both sides:

x + (14 - 14) = 17 - 14

14 - 14 = 0:

x = 17 - 14

17 - 14 = 3:

Answer: x = 3

User Russell Giddings
by
6.3k points
1 vote

Answer:

x=3

Explanation:

x+14=17

-14 -14

x=3

User Samuel MacLachlan
by
5.5k points